Análise numérica da contribuição da chave de cisalhamento em ligações pilar-viga com consolo e utilizando almofada elastomérica no apoio da viga - Chaves, Rogério José Solidario (2021)
This work aims to study the performance of the mechanism with the use of a shear key in column-beam connections, with corbel, and using elastomeric pad at the beam support, and to understand the amount of stress this mechanism contributes to the shear force resistance, as it is widespread and used in column-foundation connections, but not deeply studied in column-beam connections. Therefore, to understand this behavior is important, once its use is recommended by NBR 9062 (2017), although it does not define guidelines when the use of shear switch mechanism in the column-beam connection is required. To achieve this study purpose, it was used a methodology based on ABAQUS® computational tool, substantiated on the finite element method. First, it was done a calibration of individual elements consisted in the shear key mechanism, the elastomeric pad and the interface pillar-sheath, based on experimental tests by (Faleiros Junior 2018, Merlos 2019, Bertolucci 2010), aiming to obtain parameters for the numerical modeling of the column-beam connection in full scale, from the experimental PCD test by Faleiros Junior (2018) and the NCE test by Hadade (2016). One of the calibration highlights of individual elements were the numerical analysis results of the simple elastomeric pad, which used a rubber extrapolated constitutive model, of Rezende (2020) study, in which was validated the constitutive model for chartered supports. And with this constitutive model, it was possible to simulate numerically the experimental study of Merlos (2020). The numerical analysis results identified that the performance of the simple elastomeric pad to the compression, using the friction coefficient of μ = 0.3, approached the equations defined in NBR 9062 (2017) and with the friction of μ = 0.5 from experimental test which is used for further numerical simulations It was also possible with these calibrations, to simulate numerically the column-beam connection of the PCD and NCE models and quantify the portion of shear force absorbed by the shear key mechanism, that the PCD model with the shear key made on the face of the beam and column and the NCE model only on the column face. Additionally, a numerical study was developed for the semi-rigid connections of PCD and NCE models. Numerically, the shear key absorbed a force of 204.18 kN from a 547,32 kN absorbed by the semi-rigid connection, comparatively to the force of 220.12 kN found in the experimental test of Faleiros Junior (2018) from a 538,42 kN in the semi-rigid connection, resulting in a difference of - 7.81%. In relation to the column-beam connection moment-rotation of NCE model by Hadade (2016), it was numerically identified the bending elastic moment of 445.20 kN.m versus 397 kN.m of the experimental model, a difference of 12.14%, and such results are considered satisfactory. Thus, it was concluded that the numerical models studied adequately simulate the experimental performance of the connections and confirmed that the shear key mechanism relieves the shear forces of corbel when the elastomeric pad is used at the beam support.